CALCULATION OF RICE COMMODITY AGRICULTURAL INSURANCE PREMIUM PRICES BASED ON RAINFALL INDEX USING THE BLACK-SCHOLES METHOD - Setyapamungkas, Febriaputra; Gymnastiar, Muhammad (iora, 2024)
This study applies the Black-Scholes method to calculate rice commodity insurance premiums based on rainfall indexes. By considering rainfall fluctuations as the primary risk in rice production, the Black-Scholes method provides a more accurate and efficient estimation of insurance premiums. The research involves historical rainfall data collection and statistical analysis, resulting in realistic premium pricing. This innovative approach enhances risk management and sustainability in the rice commodity sector, benefiting stakeholders such as insurance companies and farmers. Future research should explore additional factors, including agricultural technology and government policies, for further refinement of premium calculation models.